Elasticity of enterprise: theoretical foundations and practical dimensions - Ясінська, Я (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
In the article, on the basis of the analysis in scientific and practical understanding of the notion of elasticity of an enterprise by various authors, a list of recommendations for practical use of management decisions, oriented at the formation of various components of total elasticity of and enterprise as an integral system are proposed. Peculiarities and importance of such components of total elasticity as elasticity of main and auxiliary processes, human resources, organizational structure etc. It has been demonstrated that elasticity is a multi-dimensional and a rather time-consuming parameter to be determined on the level of an entire enterprise, and because of that the capability of its generalized assessment based on the results from analyzing of elasticity of various components on different levels is an actual and an important task. It has been said that the feasibility of forming a total elasticity of an enterprise by influencing all of its possible components, especially the ones that play a dominating role in the interpretation of the elasticity of an enterprise as an integral system, has to be the topic for further research.